Self-knowledge as the basis of professional and ethical development of pedagogical workers - Ключова, Людмила (Pedagogy of Higher and Secondary Education, 2014)
Klyuchova L. S. Self-knowledge as the basis of professional and ethical development of pedagogical workers. The article deals with the content of the concept of «self-knowledge», its value for professional and ethical of development of the pedagogical worker. Highlights the role image of I-concept for the detection of positive qualities. Teacher offer to independently determine the level professional and ethical of development using: 1) questionnaire, 2) testing, 3) NLP-methods, 4) perform creative tasks. Considered NLP-method determine the type of personality and possibilities of its use of pedagogical workers in a professional activity. Components of self- knowledge is named: introspection (reflection), self esteem, self-control, self-regulation. Offer to consider self-discovery time consuming process of daily work teacher over yourself.